Komunikasi Pariwisata dalam Mendorong Keberlanjutan Destinasi Wisata: Kajian Literatur Teoretis - Ni Luh Putu Widya Astuti; Ni Made Prasiwi Bestari (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This study aims to explain the role of tourism communication in supporting sustainable tourist destination and to identify the principles, strategies, and stakeholders involved in the process. Research methods: This study employs a literature review method, analyzing academic artikels from Google Scholar, Scopus journals 2020-2025, supported by Mendeley software for reference management and source organization. Findings: Effective tourism communication is characterized by a holistic approach, transparency, evidence use, stakeholder involvement, message framing strategies, and the optimization of digital channels to support destination sustainability. Implication: These results indicate the need for more integrated and participatory tourism communication strategies to ensure consistent implementation and broader stakeholder understanding of destination sustainability.